2024 Elections and the Power Struggle: Legal and Political Perspectives - Cahyad, Aep Hendar; Wiradirja, Imas Rosidawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The 2024 elections in Indonesia will be a crucial moment that will not only determine the direction of government for the next five years, but will also demonstrate complex power dynamics from a legal and political perspective. The power struggle in the 2024 elections will involve various political actors trying to maintain or seize strategic positions in government. From a legal perspective, strict and transparent election regulations are essential to ensure a democratic process that is fair and free from fraud. Apart from that, the role of law enforcement agencies, such as the KPU and Bawaslu, in supervising election implementation is key to maintaining election integrity. From a political perspective, party coalitions, campaign strategies and mass mobilization are important factors that influence election results. Political actors must be able to develop effective strategies to win popular support while maintaining political and social stability. Apart from that, issues such as corruption, the economy and social welfare will be the main topics fought for by the candidates. The 2024 election will not only be an arena for political battles, but also a reflection of the development of democracy in Indonesia. Therefore, integrity, transparency and active community participation are important elements in determining the nation's future